Folic Acid Receptor-Mediated Targeting Enhances the Cytotoxicity, Efficacy, and Selectivity of Withania somnifera Leaf Extract: In vitro and in vivo Evidence - Yu, Yue; Wang, Jia; Kaul, Sunil C.; Wadhwa, Renu; Miyako, Eijiro (Frontiers in Oncology, 2019)
Nanomedicine holds great potential for drug delivery to achieve more effective and safer cancer treatment. We have earlier reported that the alcoholic extract of Withania somnifera leaves (i-Extract) has selective cancer cell killing activity. Herein, we developed a folate receptor-targeting i-Extract nanocomplex (FRi-ExNC) that suspends well in water and possesses enhanced selective anticancer activity in both in vitro and in vivo assays. Comparative analyses of folate receptor (FR)-positive and -negative cells revealed that FRi-ExNC caused stronger decrease in Cyclin D/Cdk4 and anti-apoptotic protein Bcl-2, as well as higher increase in growth arrest regulating protein p21WAF1 and pro-apoptotic protein PARP-1, in FR-enriched cancer cells. Our results demonstrated that FRi-ExNC could be a natural source-based nanomedicine for targeted cancer therapy.